1987
DOI: 10.1523/jneurosci.07-10-03274.1987
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of the distribution of synaptic boutons from labeled preganglionic axons on rabbit ciliary neurons

Abstract: The number of preganglionic inputs that innervate rabbit ciliary ganglion cells is directly correlated with the number of dendrites arising from each ganglion cell (Purves and Hume, 1981). In general, the innervation of multiply innervated ciliary neurons by individual preganglionic axons is regionally restricted to a portion of the postsynaptic surface that usually includes the cell body and some, but not all, of the dendrites (Forehand and Purves, 1984). These observations suggest that dendrites modulate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In neurons with a simple morphology, such as amphibian sympathetic and parasympathetic neurons that lack dendrites, a pericellular basket of boutons clearly represents the preganglionic inputs to that cell (McMahan and Kuffler, 1971;Taxi, 1976;Sargent, 1983;Streichert and Sargent, 1989). A similar arrangement occurs in simple mammalian neurons, such as those in the ciliary ganglia of rabbits (Forehand and Purves, 1984;Forehand, 1987). By analogy with these observations, it has been assumed that pericellular baskets in mammalian sympathetic ganglia, usually labelled for immunoreactivity to particular neuropeptides, also represent preganglionic inputs to the neurons they surround (e.g., Heym et al, 1984Heym et al, , 1990Lindh et al, 1986;Yamamoto et al, 1989;Gibbins, 1992;Gibbins and Matthew, 1996).…”
Section: Discussionmentioning
confidence: 93%
“…In neurons with a simple morphology, such as amphibian sympathetic and parasympathetic neurons that lack dendrites, a pericellular basket of boutons clearly represents the preganglionic inputs to that cell (McMahan and Kuffler, 1971;Taxi, 1976;Sargent, 1983;Streichert and Sargent, 1989). A similar arrangement occurs in simple mammalian neurons, such as those in the ciliary ganglia of rabbits (Forehand and Purves, 1984;Forehand, 1987). By analogy with these observations, it has been assumed that pericellular baskets in mammalian sympathetic ganglia, usually labelled for immunoreactivity to particular neuropeptides, also represent preganglionic inputs to the neurons they surround (e.g., Heym et al, 1984Heym et al, , 1990Lindh et al, 1986;Yamamoto et al, 1989;Gibbins, 1992;Gibbins and Matthew, 1996).…”
Section: Discussionmentioning
confidence: 93%
“…This result is consistent with the total number of synaptic contacts being proportional to the total surface area of the target neuron. They have further concluded that each dendrite provides a separate domain that, to a large degree, provides an exclusive synaptic target for each preganglionic input (Hume and Purves 1983;Forehand 1987). However, these earlier studies predate the recognition that different populations of preganglionic and intestinofugal inputs to sympathetic neurons can be distinguished by their patterns of neuropeptide expression.…”
Section: "Dendritic Domain" Hypothesismentioning
confidence: 99%
“…Consequently, the number of convergent synaptic inputs received by a neuron tends to be closely related to the number of dendrites it has. However, these dendritic domains are not absolute, and separate preganglionic fibers may converge onto single dendrites of autonomic final motor neurons (Forehand, 1987;Murphy et al, 1998). In the medial CG, most dendrites receive abundant convergent synapses from preganglionic and intestinofugal inputs.…”
Section: Do Dendrites Form Segregated Domains For Synapse Formation?mentioning
confidence: 99%
“…Most of the final neurons in sympathetic or parasympathetic motor pathways have relatively simple dendritic trees and receive only a small number of convergent synaptic inputs from preganglionic neurons located in the brainstem or spinal cord (Gibbins, 1995;Jä nig, 1995). On average, the number of inputs received by an autonomic final motor neuron is positively correlated with its number of primary dendrites (Purves and Hume, 1981;Hume and Purves, 1983;Forehand, 1987). The overall synaptic density is low, so that around only 1-2% of the surface of the soma and dendrites is covered with synapses.…”
mentioning
confidence: 99%